Evaluation of International Migration of Muslim Uyghurs in China to Turkiye based on interpretation Al-Jalalayn - Putra, Addarsyah Dhia; Surwandono, Surwandono (Islam Realitas: Journal of Islamic and Social Studies, 2023)
The objective of this study is to analyze the assessment of the International Migration of Uyghur Muslims from China to Turkiye, focusing on the interpretation of Al-Jalalayn. The research technique employed involves gathering data pertaining to the migration activities undertaken by Uyghur Muslims in Xinjiang. Subsequently, the data is scrutinized via the lens of Tasfir Al-Jalalayn. This study methodology employs the Living Qur’an by using data obtained from reputable sources such as Scopus, online journals, and internationally recognized and authoritative websites. The quality of the data and the methodologies used for data gathering are ensured by the utilization of the Publish or Perish tool. The research findings presented in this study pertain to the unique circumstances surrounding international immigration for the Uyghur Muslim population residing in Xinjiang. The study establishes a connection between the processes of isolation or migration and the potential for improved quality of life. The aforementioned perspective is derived from the Al-Jalalayn Book's interpretation of certain Quranic passages, including Surah An-Nisa verses 97 and 100 and At-Tawbah verse 40. These verses convey an exhortation to relocate to a more favorable environment to evade adverse circumstances like violence, injustice, and threats that may be prevalent in their current location. Similarly, Uyghur Muslims who relocated to Turkiye improved conditions regarding security, access to justice, and socioeconomic opportunities.Tujuan dari penelitian ini adalah untuk menganalisis penilaian Migrasi Internasional Muslim Uyghurdari Cina ke Turki, dengan fokus pada penafsiran Al-Jalalayn. Teknik penelitian yang digunakan adalah dengan mengumpulkan data-data yang berkaitan dengan kegiatan migrasi yang dilakukan oleh Muslim Uyghur di Xinjiang. Selanjutnya, data-data tersebut diteliti melalui lensa tafsir Al-Jalalayn. Metodologi penelitian ini menggunakan Living Qur'an, dengan menggunakan data yang diperoleh dari sumber-sumber terkemuka seperti Scopus, jurnal online, dan situs-situs yang diakui secara internasional yang dapat diverifikasi. Kualitas data dan metodologi yang digunakan untuk pengumpulan data dipastikan dengan penggunaan alat Publish or Perish. Temuan penelitian yang disajikan dalam penelitian ini berkaitan dengan keadaan unik seputar imigrasi internasional untuk populasi Muslim Uyghur yang tinggal di Xinjiang. Penelitian ini membangun hubungan antara proses isolasi atau migrasi dan potensi peningkatan kualitas hidup. Perspektif yang disebutkan di atas berasal dari penafsiran Kitab Al-Jalalain terhadap ayat-ayat Alquran tertentu, termasuk Surat An-Nisa ayat 97 dan 100, serta At-Taubah ayat 40. Ayat-ayat ini menyampaikan anjuran untuk pindah ke lingkungan yang lebih baik untuk menghindari keadaan yang tidak menguntungkan seperti kekerasan, ketidakadilan, dan ancaman yang mungkin lazim terjadi di lokasi mereka saat ini. Demikian pula, Muslim Uyghur yang pindah ke Turki mengalami kondisi yang lebih baik dalam hal keamanan, akses terhadap keadilan, dan peluang sosial ekonomi.